Phenazine Antibiotic‐Inspired Discovery of Bacterial Biofilm‐Eradicating Agents. (2nd October 2019) - Huigens, Robert W.; Abouelhassan, Yasmeen; Yang, Hongfen
Abstract: Bacterial biofilms are surface‐attached communities of slow‐growing and non‐replicating persister cells that demonstrate high levels of antibiotic tolerance. Biofilms occur in nearly 80 % of infections and present unique challenges to our current arsenal of antibiotic therapies, all of which were initially discovered for their abilities to target rapidly dividing, free‐floating planktonic bacteria. Bacterial biofilms are credited as the underlying cause of chronic and recurring bacterial infections. Innovative approaches are required to identify new small molecules that operate through bacterial growth‐independent mechanisms to effectively eradicate biofilms. One source of inspiration comes from within the lungs of young cystic fibrosis (CF) patients, who often endure persistent Staphylococcus aureus infections. As these CF patients age, Pseudomonas aeruginosa co‐infects the lungs and utilizes phenazine antibiotics to eradicate the established S. aureus infection. Our group has taken a special interest in this microbial competition strategy and we are investigating the potential of phenazine antibiotic‐inspired compounds and synthetic analogues thereof to eradicate persistent bacterial biofilms. To discover new biofilm‐eradicating agents, we have established an interdisciplinary research program involving synthetic medicinal chemistry, microbiology and molecular biology. From these efforts, we have identified a series of halogenated phenazines (HPs) that potently eradicate bacterial biofilms, and future work aims to translate these preliminary findings into ground‐breaking clinical advances for the treatment of persistent biofilm infections. Abstract : Inspired by phenazine antibiotic natural products, our group has discovered and developed a series of tunable halogenated phenazines that demonstrate potent biofilm eradication activities. Recently, one halogenated phenazine was used as a probe molecule in mechanistic studies in MRSA biofilms using RNA‐seq technology, and ongoing efforts are directed at prodrug development for translational purposes.